The little village of book lovers ebook A novel. - George, Nina (2023)
A young woman with the extraordinary power to bring soulmates together searches for her own true love in this tender, lyrical standalone novel inspired by the “bona fide international hit” ( The New York Times Book Review ) The Little Paris Bookshop In Nina George’s New York Times bestseller The Little Paris Bookshop, beloved literary apothecary Jean Perdu is inspired to create a floating bookstore after reading a seminal pseudonymous novel about a young woman with a remarkable gift. The Little Village of Book Lovers is that novel. “Everyone knows me, but none can see me. I’m that thing you call love.” In a little town in the south of France in the 1960s, a dazzling encounter with Love itself changes the life of infant orphan Marie-Jeanne forever. As a girl, Marie-Jeanne realizes that she can see the marks Love has left on the people around her—tiny glowing lights on the faces and hands that shimmer more brightly when the one meant for them is near. Before long, Marie-Jeanne is playing matchmaker, bringing true loves together in her village. As she grows up, Marie-Jeanne helps her foster father, Francis, begin a mobile library that travels throughout the many small mountain towns in the region of Nyons. She finds herself bringing soulmates together every place they go—and there are always books that play a pivotal role in that quest. However, the only person that Marie-Jeanne can’t seem to find a soulmate for is herself. She has no glow of her own, though she waits and waits for it to appear. Everyone must have a soulmate, surely—but will Marie-Jeanne be able to recognize hers when Love finally comes her way?